PEREMPUAN DAN PENDIDIKAN ISLAM DALAM PERSPEKTIF KONTEMPORER - Ronika Putra; M. Fikar; Amrizon; Suhaimis; Rusydi AM; Riki Saputra; Mursal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the role of women in Islamic education from historical and contemporary perspectives, as well as the challenges they face in accessing education. The main focus of the research is to describe women's contributions to Islamic education, identify barriers limiting their participation, and formulate strategies to strengthen gender-responsive Islamic education. The research methodology employs a qualitative approach, utilizing data collection techniques such as literature review, in-depth interviews, and field observations. Data were analyzed thematically with source triangulation to ensure the validity of the results. The findings indicate that Islam provides an egalitarian foundation for women in education, as reflected in the Qur’an and Hadith. However, social practices influenced by patriarchal culture often restrict women’s access to education. In the modern era, women have begun to play significant roles as educators, writers, and activists, yet they still face challenges such as conservative textual interpretations, technological access disparities, and limited representation in formal institutions. Strategies for empowerment include integrating gender perspectives into curricula, enhancing the capacity of female religious leaders, and leveraging digital technology.